STEM Trends in Physics Education Research at The Secondary School Level In Indonesia: A Bibliometric Perspective (2010–2024) - Barus, Carolina Sri Athena; Ringo, Sariaman Siringo; Sitepu, Junita Elviani; Siallagan, Zen Ladestam (Universitas Negeri Semarang, 2025)
Science, Technology, Engineering, and Mathematics (STEM) education has attracted growing global attention, yet its development within physics learning in Indonesia remains unevenly mapped. This study conducts a bibliometric analysis of STEM-oriented physics education in Indonesian secondary schools (2010–2024). Articles were retrieved using Publish or Perish (Google Scholar), curated in Mendeley, and analyzed with VOSviewer. Fifty-four eligible journal articles were identified. The findings indicate that research on STEM-oriented physics learning expanded rapidly, peaking in 2020, and subsequently fluctuated at levels above those observed before 2018. East Java was identified as the most productive province in STEM education research related to physics learning. Furthermore, the University of Jember and the State University of Malang are the two most active institutions in publishing articles in this field. Based on keyword analysis, STEM research in physics learning predominantly focuses on the development of teaching materials, instructional models, learning outcomes, and physics subject content. Among the ten most-cited articles, four discuss STEM project-based learning. This study maps the national research landscape, providing an empirical foundation for researchers, educators, and policymakers to identify gaps, refine STEM strategies, and promote evidence-based practices. Practically, the field would benefit from broader multi-site collaborations (including regions beyond Java), more rigorous methodological reporting, and the systematic adoption of technology-enhanced resources.